Identification of Biomarkers Based on Starvation Response-Related Genes for Assessing the Immune Profile and Prognosis in Lung Adenocarcinoma - Xixian Lou; Hui Xia; Zongxiao Shangguan; Lianmin Bao; Heping Lin (International Journal of Genomics)
Conclusion: This study identified three key lncRNAs related to starvation response and created a risk model that can accurately assess the prognosis and immune characteristics in LUAD, offering novel biomarkers and a theoretical basis for the precision immunotherapy and targeted intervention in LUAD.